The combination of a tyrosine kinase inhibitor and blinatumomab in patients with Philadelphia chromosome–positive acute lymphoblastic leukemia or Philadelphia chromosome‐like acute lymphoblastic leukemia - Xiaoxia Wu; Shenqi Lu; Xinhui Zhang; Zhen Yang; Aining Sun; Depei Wu; Huifen Zhou; Miao Miao (Cancer Medicine, 2024)
Abstract Tyrosine kinase inhibitors (TKIs) have revolutionized Philadelphia chromosome‐positive (Ph+) acute lymphoblastic leukemia (ALL) treatment. The combination of blinatumomab and a TKI in the frontline setting has shown the safety and efficacy of the chemotherapy‐free treatment approach in patients with Ph + ALL. This retrospective analysis included 19 patients with Ph + ALL and Ph‐like ALL treated with the combination of blinatumomab and a TKI. Of the 14 newly diagnosed patients, the overall response, complete remission (CR), and molecular response (CMR) rates after one cycle of blinatumomab were 100% (10/10), 90% (9/10), and 57% (8/14), respectively. Of the five relapsed patients, the CR and CMR rates were 50% (2/4) and 40% (2/5). Blinatumomab in combination with TKIs is safe and effective and hence this combination therapy could be a viable therapeutic option in front‐line treatment of patients with Ph + ALL.